First Trimester Renin and Aldosterone Levels of Pregnant Women With Prognosis of Preeclampsia and/or Related Adverse Pregnancy Outcomes - (:unkn) unknown (My University, 2017)
0

Objective: To evaluate the first-trimester renin and aldosterone levels in pregnancies complicated by prognosis of preeclampsia and/or related adverse pregnancy outcomes.Methods: We measured serum levels of renin and aldosterone in pregnant women for first trimester screening test. Total of 180 pregnant women were included in the study and 144 of them completed the study. All pregnant women were followed during pregnancy for preeclampsia and related complications. Renin and aldosterone levels in preeclampsia and/or poor obstetric prognosis group were compared with normal pregnancy outcome group.Results: Preeclampsia developed in 13 pregnant women and one or more poor obstetric outcome developed in 36 women. Renin and aldosterone levels were not significantly different in preeclamptic women or those with poor obstetric outcome compared with the controls.Conclusion: We think that maternal first trimester renin and aldosterone levels do not have a role in the pathogenesis and prediction of preeclampsia
Keywords: Genel ve Dahili Tıp